Numerical Study of Damper Plate and Nozzle Effect on Vortex Turbine Basin for Increasing Flow Kinetic Energy Entering Turbine Rotor - Herman Sasongko; Wildan Alfa Rahman (JMES The International Journal of Mechanical Engineering and Sciences, 2023)
The Gravitational Water Vortex Power Plant (GWVPP) is a small-scale hydroelectric power generator that makes use of the energy generated from a vortex flow to turn turbine blades and generate electricity. In this research study, the focus was on the numerical analysis of the basin design of the GWVPP, which is divided into three sections: vortex generator section, transformer section, and turbine section. To support the transformation process from tangential vortex speed to axial vortex speed in the transformer section, a damper plate was installed to direct the rotating flow. The effect of the nozzle in accelerating the flow for optimizing the basin design was also studied to reduce blockage caused by the transformation process. The numerical results indicate that designs with nozzle have lower velocity outputs due to blockage from the rotating flow. At flow rate of 0.1 m3/s, the presence of damper plate reduces the maximum flow rotation, but at flow rate of 0.2 m3/s, it prevents flow leakage on the surface. The basin design without damper plate and nozzle is the optimal variation for flow rates of 0.1 m3/s, while the design with damper plate but without nozzle is optimal for flow rates of 0.2 m3/s.